1970
DOI: 10.1063/1.1673243
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen–Deuterium Self-Exchange in Hydrogen Sulfide and Hydrogen Selenide as Studied with a Pulsed-Molecular-Beam Quadrupole Mass Filter

Abstract: Articles you may be interested inMolecular beam study of the mechanism of catalyzed hydrogen-deuterium exchange on platinum single crystal surfaces J. Chem. Phys. 62, 3149 (1975); 10.1063/1.430862Equilibrium constants of hydrogen-deuterium-tritium selfexchange reactions in water vapor as studied with a pulsed molecularbeam quadrupole mass filterThe equilibrium constants for hydrogen-deuterium self-exchange in hydrogen sulfide and hydrogen selenide have been studied over a wide range of deuterium atom percent u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1971
1971
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Table 5 The comparison of equilibrium constant K calculated from this study and those from Wolfsberg et al (1970), Bron et al (1973), Richet et al (1977) and experiments. Wolfsberg et al (1970) and Bron et al (1973) Richet et al (1977 This study Experiments Friedman and Shiner(1966); (b) Pyper and Christensen (1975); (c) Pyper and Newbury (1970); (d) Richet et al (1977); (e) Bron et al (1973).…”
Section: Equilibrium Constant K With Corrections Beyond Harmonic Levelmentioning
confidence: 92%
See 1 more Smart Citation
“…Table 5 The comparison of equilibrium constant K calculated from this study and those from Wolfsberg et al (1970), Bron et al (1973), Richet et al (1977) and experiments. Wolfsberg et al (1970) and Bron et al (1973) Richet et al (1977 This study Experiments Friedman and Shiner(1966); (b) Pyper and Christensen (1975); (c) Pyper and Newbury (1970); (d) Richet et al (1977); (e) Bron et al (1973).…”
Section: Equilibrium Constant K With Corrections Beyond Harmonic Levelmentioning
confidence: 92%
“…For the water vapor internal equilibrium reaction: H 2 O + D 2 O = 2HDO, large deviations were found between theoretical studies and experiments (Pyper et al, 1967;Pyper and Newbury, 1970;Pyper and Christensen, 1975). Wolfsberg (1969) showed that it was not sufficiently accurate to add anharmonic corrections without the contributions of G 0 terms to partition function ratios.…”
Section: Equilibrium Constant K With Corrections Beyond Harmonic Levelmentioning
confidence: 93%
“…Unfortunately, we cannot unambiguously confirm the theory on the basis of the present work. However, in previous tests of the theory using isotopic self-exchange reactions (NH3 [10], H2S [3,7], H2Se [3,7], and the tritiated water reactions [5]) the intensity ratios agreed with the theoretical squilibrium constant. It is hoped that this paper might stimulate others to devise a method to test the theory with more precision.…”
Section: Discussionmentioning
confidence: 70%
“…[5] but disagree with those in Refs. [1][2][3][4], (See Table 1 The iteration computer code also calculated the sensitivity ratio, S., at seven different times. The ratios are shown in Table 5.…”
Section: Results and Discussion'mentioning
confidence: 99%
See 1 more Smart Citation